Gland- and cell-level heterogeneity in the prostate: A narrative review of related diseases - Gang Wang; Cai Lv; Zhenxiang Liu; Mengxing Huang; Yu Zhang; Jing Chen; Jinyue Hu; Yiling Jin; Zhiming Bai (Current Urology, 2025)
Abstract. Because of the anatomical characteristics of the prostate, benign prostatic hyperplasia (BPH) often occurs in the transition zone, whereas prostate cancer (PCa) tends to occur in the peripheral zone. This distribution characteristic indicates that the prostate gland has cell type and distribution heterogeneity. However, the current research cannot answer these questions precisely. As research has progressed, the significance of many newly discovered cell types for the treatment of BPH and PCa has sparked widespread concern. Prostate heterogeneity is closely associated with gland development and formation and the regional distribution of the disease. Prostate heterogeneity can be observed at the gland and cell levels and determines disease distribution, presentation, and characteristics, including changes in the microenvironments of BPH and PCa. Cell population interactions promote disease onset and development; single-cell sequencing techniques may help elucidate specific cell types and gene expression patterns in different prostate zones. The stem cell characteristics of club/hillock cells and the inflammatory environment induced by immune cells offer alternative interpretations of the pathogenic mechanisms of BPH and PCa, and molecular omics studies can help identify novel avenues for treatment development.